2012
DOI: 10.7326/0003-4819-156-1-201201030-00002
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Manipulation, Medication, or Home Exercise With Advice for Acute and Subacute Neck Pain

Abstract: National Center for Complementary and Alternative Medicine, National Institutes of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(115 citation statements)
references
References 55 publications
3
105
0
7
Order By: Relevance
“…16 Bronfort et al's 17 study included 272 participants, between the ages of 18 and 65 years, who had subacute, non-specific neck pain for 2-12 weeks. 17 Bronfort et al 17 also yielded a high quality score (16/19). They found that the intervention group, which included advice, basic anatomy, postural instructions, demonstrations of daily actions, and a HEP, had a larger effect on the Pain Scale when compared to medication or spinal manipulation (effect sizes of 0.11 and 0.16, respectively).…”
Section: 18mentioning
confidence: 99%
See 4 more Smart Citations
“…16 Bronfort et al's 17 study included 272 participants, between the ages of 18 and 65 years, who had subacute, non-specific neck pain for 2-12 weeks. 17 Bronfort et al 17 also yielded a high quality score (16/19). They found that the intervention group, which included advice, basic anatomy, postural instructions, demonstrations of daily actions, and a HEP, had a larger effect on the Pain Scale when compared to medication or spinal manipulation (effect sizes of 0.11 and 0.16, respectively).…”
Section: 18mentioning
confidence: 99%
“…Bronfort et al 17 was the only study to not indicate adherence. Adherence to the prescribed HEP was measured in six of the seven studies using means such as training diaries 11,[19][20][21] and questionnaires.…”
Section: 1821mentioning
confidence: 99%
See 3 more Smart Citations